Strategi Penanganan dan Pencegahan Stunting Di Desa Jebak - Mahdayeni; Dian Puspitasari; Zilawati; Dian Puspitasari; Laila Agustin; Windah Pebriyanti; Arrahman; Bayu Prasetyo Putra (Jurnal Pelita Pengabdian Masyarakat, 2024)
Abstrak Stunting describes a state of chronic malnutrition during growth and development from early life. the results of a health survey in Indonesia in 2013, 37.2% of young children experienced stunting. Of this percentage, 19.2% of children were classified as short and 18.0% were very short. The prevalence of stunting has increased compared to the 2010 Riskesdas results, namely 35.6. The nutritional condition of pregnant women also greatly affects the health and development of the fetus. Impaired growth in the uterus can cause low birth weight. Babies with low birth weight have a greater risk of stunting. The baby's body length at birth is also related to the prevalence of stunting. Apart from that, another factor that triggers stunting is the lack of breast milk intake for babies during the first 6 months of life. Keywords: stunting, prevention, treatment